2011
DOI: 10.1080/16506073.2011.580367
|View full text |Cite
|
Sign up to set email alerts
|

Five Facets Mindfulness Questionnaire—Reliability and Factor Structure: A Swedish Version

Abstract: Two studies were conducted to assess the Swedish version of the Five Facets Mindfulness Questionnaire (FFMQ), which was originally created by Baer et al. (2006). The aim of Study 1 was to examine the psychometric properties of the FFMQ using data from 495 individuals. Quantitative and qualitative analyses resulted in a reduction of the scale by 10 items. Psychometric properties, including internal consistency of the revised instrument, were examined. The Swedish FFMQ provides results comparable to those obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 14 publications
8
90
0
Order By: Relevance
“…The original version of the FFMQ has shown good psychometric properties (Baer et al 2006;Baer et al 2008), and the Swedish translation of the FFMQ (Lilja et al 2009) has shown similar results. Cronbach's alpha coefficients for the Swedish version of the FFMQ total scale and its' five subscales ranged from 0.80 to 0.92 (Lilja et al 2009). In this study, Cronbach's alpha coefficients ranged from 0.80 (Nonreactivity to inner experience) to 0.88 (Describe).…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…The original version of the FFMQ has shown good psychometric properties (Baer et al 2006;Baer et al 2008), and the Swedish translation of the FFMQ (Lilja et al 2009) has shown similar results. Cronbach's alpha coefficients for the Swedish version of the FFMQ total scale and its' five subscales ranged from 0.80 to 0.92 (Lilja et al 2009). In this study, Cronbach's alpha coefficients ranged from 0.80 (Nonreactivity to inner experience) to 0.88 (Describe).…”
Section: Methodsmentioning
confidence: 54%
“…The Five Facet Mindfulness Questionnaire To measure self-reported mindfulness, the Swedish version of the FFMQ was used (Lilja 2009). The FFMQ is designed to measure mindfulness skills in daily life and consists of 39 statements using a 1-5 Likert scale ranging from Never or very rarely true to Very often or always true.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores on each subscale indicate higher levels of each facet of trait mindfulness. The FFMQ has demonstrated good internal consistency in previous young adult samples (Cronbach's a ranging from .79 to .93; Caldwell, Harrison, Adams, Quin, & Greeson, 2010), as well as good construct validity across several studies (Baer et al, 2008;Heeren, Douilliez, Peschard, Debrauwere, & Philippot, 2011;Lilja et al, 2011;Van Dam, Earleywine, & Danoff-Burg, 2009). Further studies of 6…”
Section: Trait Mindfulnessmentioning
confidence: 89%
“…Baer et al 35 reported adequate to good internal consistencies (ranging from .72 to .92) for each of the scales. The FFMQ has been validated in several countries, [35][36][37][38][39][40] including Norway 41 In this study Cronbach's alpha was .81 for the disaster-exposed group, .66 for the control group, and .75 for the total group.…”
Section: The Five-facet Mindfulness Questionnaire (Ffmq)mentioning
confidence: 99%